Implementasi Pendidikan Karakter dalam Kurikulum Merdeka di Sekolah Dasar - Yayu, Indah Putri; Haifaturrahmah; Muhdar, Syafruddin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the implementation of character education within the Kurikulum Merdeka at the elementary school level. Character education is a central component of the curriculum, designed to foster students’ holistic development, encompassing academic, moral, social, and personal dimensions. Specifically, this research analyzes how character education is integrated into classroom practices, identifies challenges encountered in its implementation, and explores opportunities for strengthening its application. The study employs a descriptive qualitative approach, with data collected through classroom observations, interviews with teachers, and analysis of curriculum-related documents. The findings reveal that character education is implemented through project-based learning, contextual activities, and collaboration among teachers, parents, and the community. These strategies contribute to the development of students’ 4C competencies collaboration, communication, critical thinking, and creativity while instilling essential character values. However, several challenges persist, including limited teacher training, inadequate supporting facilities, and varying levels of parental involvement. Despite these constraints, opportunities for improvement exist through enhanced professional development programs, improved educational infrastructure, and more systematic character assessment practices